Analysis of dog movement using a single accelerometer in different body positions—a new approach - Reinstein, Rainer da Silva; Pozzobon, Franciéli Mallmann; Caye, Pâmela; Paraguassú, Amanda Oliveira; Socolhoski, Brenda Viviane Götz; Schiefler, Otávio Henrique de Melo; Pozzobon, Ricardo; Müller, Daniel Curvello de Mendonça; Brun, Maurício Veloso (Frontiers in Veterinary Science, 2025)
IntroductionThe analysis of canine locomotion has significantly advanced over the past few decades with the advent of technologies that enable more precise measurements. Traditional methods, such as force platforms and three-dimensional kinematic systems, though accurate, are often costly and require specialized equipment, limiting their broader application. This study aims to evaluate an alternative approach using a single triaxial accelerometer positioned in different anatomical regions (neck, sternum, pelvis, and right knee) to analyze gait patterns in healthy dogs.MethodsTwenty-four clinically healthy dogs were used, divided into two groups based on body weight: ≤ 15 kg (G−15) and >15 kg (G+15). A wireless triaxial accelerometer sensor was utilized. Acceleration data were collected during walking and trotting in different anatomical positions: neck, sternum, pelvis, and right knee. The data were processed using Fourier analysis to extract harmonic frequencies and analyzed for acceleration peaks and autocorrelation to assess gait symmetry.ResultsThe findings showed that larger and heavier dogs (G+15) exhibited lower movement frequencies and more stable patterns, especially during trotting, while smaller and lighter dogs (G−15) demonstrated higher frequencies and greater variability. Significant differences in acceleration peaks were observed between body regions, with the pelvis and knee showing the highest values. However, harmonic frequencies did not vary significantly between the different anatomical regions. The autocorrelation analysis revealed that, in larger dogs, the sternum and pelvis regions presented greater consistency, indicating enhanced stability during locomotion.DiscussionThese findings suggest that using a single accelerometer in different body regions is a practical and effective methodology for gait analysis in dogs, allowing the identification of locomotion differences among dogs of varying sizes and movement phases. This approach offers an accurate alternative for veterinary biomechanical studies, with potential clinical applications in the diagnosis and monitoring of gait abnormalities. The use of a single triaxial accelerometer proved effective for canine gait analysis, revealing differences by body weight. The sternum and pelvis are ideal monitoring regions, suggesting applications in biomechanical and clinical studies.